Context-dependent data envelopment analysis with common set of weights. Issue 3 (3rd July 2018) - Zhu, Weiwei; Sun, Panpan; Zhang, Qian
ABSTRACT: The original context-dependent data envelopment analysis measures the attractiveness and progress of decision-making units (DMUs) through calculating the radial distance between the DMU under evaluation and the evaluation context. It only shows how distinct the DMU is from a single specific virtual DMU on the evaluation context, and ignores the entire evaluation context. In this paper, we incorporate the common set of weights into the original context-dependent data envelopment analysis. This improvement ensures evaluation consistency via providing an overall evaluation context.